Polymeric Gas-Separation Membranes for Petroleum Refining - Yousef Alqaheem; Abdulaziz Alomair; Mari Vinoba; Andrés Pérez (International Journal of Polymer Science)
Polymeric gas-separation membranes were commercialized 30 years ago. The interest on these systems is increasing because of the simplicity of concept and low-energy consumption. In the refinery, gas separation is needed in many processes such as natural gas treatment, carbon dioxide capture, hydrogen purification, and hydrocarbons separations. In these processes, the membranes have proven to be a potential candidate to replace the current conventional methods of amine scrubbing, pressure swing adsorption, and cryogenic distillation. In this paper, applications of polymeric membranes in the refinery are discussed by reviewing current materials and commercialized units. Economical evaluation of these membranes in comparison to traditional processes is also indicated.